Drivers affecting adoption of forest landscape restoration among smallholder farmers in Central Togo - Hounkpati, Kossi; Moluh Njoya, Hamza; Adjonou, Kossi; Kokou, Kouami; Sieber, Stefan; Löhr, Katharina (Frontiers in Sustainable Food Systems, 2024)
One possible solution for regaining ecological functionality and enhancing human well-being in deforested and degraded landscapes is Forest Landscape Restoration (FLR). Togo has set a goal to restore 1.4 million hectares of lands by 2030. Despite the national commitment to FLR, no significant progress has been made and drivers that impact FLR adoption remain poorly understood. Thus, it is crucial to enhance knowledge on drivers influencing the adoption of FLR to facilitate its implementation while also providing recommendations for policy and practice. Surveying 494 Togolese smallholder farmers, this study focuses on socio-economic, biophysical, geographical, and institutional aspects of FLR as well as farmers’ perceptions. Descriptive statistics and logistic regression are employed to provide a model of the drivers affecting FLR in Togo. The results reveal that 43.62% of smallholder farmers adopt FLR practices in the study areas. FLR practices linked to agricultural land restoration, such as improved fallow and crop rotation system (33.40%) and agroforestry (32.19%), are the most widely adopted, followed by reforestation (13.36%), community forest creation (8.7%), commercial forest plantation (7.29%), and sacred forest enrichment (2.83%). Results also indicate that smallholder farmers in cooperatives and involved in restoration activities have a higher awareness of the importance of restoration and willingness to adopt practices. Similar observations are made for farmers living in a zone with high exposure to FLR activities. Secure property rights also support adopting FLR practices. Further, the services of local technicians or facilitators create favorable conditions that encourage smallholders to implement FLR practices. Perception of restoration practices and need, motivation for maintaining restoration practices, and relevance for food security greatly impact smallholder farmer adoption. These results suggest that FLR practices can be increased through training and access to seedlings, supporting reforestation and community forest creation by incentivizing smallholder participation through subsidies or technical assistance, clarifying and strengthening smallholders’ land rights, and deploying more local technicians.